Masalah pembangunan manusia: Dari kependudukan, pengangguran, wanita, hingga migrasi - Mudrajad Kuncoro (Universitas Islam Indonesia, 1997)
In the fast decade, development paradigm shifted from production centered oriented (PCO) to people centered development (PCD). The PCO puts human being as a factor among the of her production factors, while in the PCD. human being at once being viewed as a dominant object and subject of the development project. This last concept usually called the development with humanity insight. Some major problems in the human being development in Indonesia are about population, unemployment, women and migration. Population affairs, as predicted, will tend to influence development planning, for example: the falling of the growth, ripen structure, high rural population, the rising of educational quality, etc. The unemployment of the youth is also noted as a critical problem. At the same time, there is a large numbers of women entering into the work force that need to be thought seriously, because their work composition, status and work hour are marginal. The third problem discusses here is the urbanization. it is found here that the urbanization in Indonesia is still premature and creating complex problems that should be solved.